Gaya Sarkasme Tokoh dalam Film Rumah untuk Alie: Kajian Stilistika - Tasya Madinah; Fitri Amilia; Astri Widyaruli Anggraeni (Jurnal Ilmiah Global Education, 2026)
This study aims to describe the forms and functions of sarcastic language style used by the characters in the film Rumah untuk Alie through a stylistic approach based on Keraf’s (2006) theory of language style. This research employs a qualitative method with listening and note-taking techniques to collect data in the form of utterances containing sarcasm. The data were analyzed using the referential identity method (metode padan) to interpret meanings, contexts, and rhetorical functions of sarcasm in shaping characters and conflicts. The findings reveal three main forms of sarcastic language style: mocking sarcasm, cursing sarcasm, and ironic sarcasm. Each form serves different rhetorical purposes, such as expressing emotions, channeling anger, and asserting social dominance within conflictual interactions. Stylistically, the use of sarcasm in the film demonstrates how diction, intonation, and context create emotional and aesthetic effects while reflecting the characters’ social dynamics and power relations. This study concludes that language in film functions not merely as a medium of communication but also as a means of psychological expression and social representation.